Feelings and family burden in the care of older adults with Alzheimer’s: integrative literature review - Cruz, Luma Maria; Ribeiro, João (Brazilian Journal of Global Health, 2021)
OBJETIVO: Identificar na literatura científica nacional quais as dificuldades que a família enfrenta no cuidado de idosos com Doença de Alzheimer (DA). MÉTODOS: Revisão integrativa da literatura realizada entre os meses de março e setembro de 2020 no Portal Regional da Biblioteca Virtual de Saúde (BVS) e no diretório de revistas Scientific Electronic Library Online (SciELO) utilizando descritores contidos no DECS e palavras-chave, respeitando as características do portal e do diretório. RESULTADOS: Quinze estudos foram selecionados, lidos na íntegra e criadas duas categorias por similaridade de conteúdo, a saber: (1) Desgaste dos cuidadores familiares – Do sentimento de prisão à sobrecarga gerada pelo cuidado; (2) Relações familiares e sentimentos relacionados ao cuidado. CONCLUSÃO: O cuidado se baseia em amor, afeto, reconhecimento e retribuição. Criar uma rede de cuidados para toda família faz-se necessário a fim de amenizar o sofrimento de toda família. DESCRITORES: Idoso, Doença de Alzheimer, Cuidado familiar, Relações familiares, Emoções. ABSTRACT OBJECTIVE: Identify in the national scientific literature what difficulties the family faces in the care of elderly people with Alzheimer's Disease (AD). METHODS: Integrative literature review carried out between the months of March and September 2020 on the Regional Portal of the Virtual Health Library (VHL) and on the directory of Scientific Electronic Library Online (SciELO) journals using descriptors contained in the DECS and keywords, respecting the characteristics of the portal and the directory. RESULTS: Fifteen studies were selected, read in full and two categories were created for similarity of content, namely: (1) Weariness of family caregivers - From the feeling of imprisonment to the burden generated by care; (2) Family relationships and feelings related to care. CONCLUSION: Care is based on love, affection, recognition and retribution. Creating a care network for the whole family is necessary in order to alleviate the suffering of the whole family. DESCRIPTORS: Aged, Alzheimer Disease, Family care, Family Relations, Emotions.